HISTOPATHOLOGICAL LESIONS INDUCED BY COPPER SULPHATE IN HEPATOPANCREAS OF MOLLIENESIA S’P. - Sultan, Salim; Khan, S Mahmood (Indian Journal of Fisheries, 2011)
The living specimens of Mollienesia sp. (35 to 45 mmin length) were purchased from an aquarist. Delhi.